2014
DOI: 10.1103/physrevlett.112.088301
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Response of a Complex Fluid at Intermediate Distances

Abstract: The viscoelastic response of complex fluids is length-and time-scale dependent, encoding information on intrinsic dynamic correlations and mesoscopic structure. We study the length scale above which bulk viscoelasticity sets in, and the material response that precedes it at shorter distances. We show that the crossover between these two regimes may appear at a surprisingly large distance. We generalize the framework of microrheology to include both regimes and apply it to F-actin networks, thereby extracting t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 28 publications
5
93
0
Order By: Relevance
“…(18), depending on the fluid viscosity η and characteristic pore size ξ. Hence, ξ is identified with the network's mesh size [10], up to a proportionality factor close to unity [12,13]. It also characterizes the spatial decay of transverse (shear) stresses due to the friction between the two components and, therefore, decreases with increasing Γ .…”
Section: Decoupled Flowsmentioning
confidence: 99%
See 4 more Smart Citations
“…(18), depending on the fluid viscosity η and characteristic pore size ξ. Hence, ξ is identified with the network's mesh size [10], up to a proportionality factor close to unity [12,13]. It also characterizes the spatial decay of transverse (shear) stresses due to the friction between the two components and, therefore, decreases with increasing Γ .…”
Section: Decoupled Flowsmentioning
confidence: 99%
“…Theoretical arguments given in ref. [12] showed that the intermediate response was fundamentally different from the macroscopic one, in that it was related to mass transport, rather than momentum transport, of the fluid. As we shall see below, the intermediate region corresponds to the relative motion of the material's two components (network and solvent), whereas in the asymptotic region the material moves collectively, as a whole.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations